The effects of high intensity interval training on resting mean arterial pressure and C-reactive protein content in prehypertensive subjects - Skutnik, Benjamin C. (Kansas State University, 2013)
Subjects with prehypertension are at risk for developing hypertension (HTN). Hypertension is associated with low-grade systemic inflammation (LGSI). Aerobic exercise training (ET) is a proven means to reduce both blood pressure and LGSI in healthy and diseased subjects. Recently, high intensity interval training (HIIT) has been show to elicit similar cardiovascular and metabolic adaptations as ET in healthy and at-risk populations in a more time efficient manner. Therefore, we hypothesized that HIIT would elicit greater reductions in blood pressure and LGSI than ET. Twelve pre-hypertensive subjects (systolic blood pressure 127.0 ± 8.5 mmHg; diastolic blood pressure 86.2 ± 4.1 mmHg) were randomly assigned to an ET group (n=5) and a HIIT group (n=7). All subjects performed an incremental test to exhaustion (VO2max) on a cycle ergometer prior to, after 4 weeks, and after 8 weeks of training. Resting heart rate and blood pressure were measured prior to and three times a week during training. LGSI was measured via high-sensitivity C-reactive protein (hs-CRP) prior to, after 4 weeks and after 8 weeks of training. ET subjects performed an eight week exercise training program at 40% VO2 reserve determined from the VO2max test, while HIIT subjects performed exercise at 60% peak power determined from the VO2max test. ET group trained four days/week while HIIT trained three days/week. ET exercised for 30 minutes continuously at a constant workload and cadence of 60 rpm while HIIT performed a protocol on a 1:1 work-to-rest ratio at a constant workload and cadence of 100 rpm. Both groups showed similar (p<0.05) decreases in mean arterial (ET = -7.3%, HIIT = -4.5%), systolic (ET = -6.6%, HIIT = -8.8%), and diastolic (ET= -9.7, HIIT= -8.2%) blood pressure. HIIT decreased in LGSI (-33.7%) while ET did not change LGSI (p>0.05). VO2max increased ~25% with both HIIT and ET with no differences (p>0.05) between groups. These data suggest both HIIT and ET similarly decreased resting blood pressure and increased VO2max while HIIT was effective in decreasing LGSI in subjects who were pre-hypertensive.
Keywords: Hypertension; High intensity interval training; Systemic inflammation; Prehypertension; Physiology (0719)